Unido III—A preview - Manfred Stegger (Intereconomics, 1979)
The Third UN Conference for Industrial Development (UNIDO III) will be held in New Delhi on January 21-February 8, 1980. Which demands will the developing countries address to the industrial countries on this occasion? And what are the chances of these demands being met?
Keywords: 330